2014
DOI: 10.1080/01635581.2015.976312
|View full text |Cite
|
Sign up to set email alerts
|

Oral Nutritional Support Can Shorten the Duration of Parenteral Hydration in End-of-Life Cancer Patients: A Randomized Controlled Trial

Abstract: Tube feeding or hydration is often considered for end-of-life cancer patients despite the negative effects on quality of life. The efficacy of oral nutritional support in this setting is unknown. We conducted a randomized trial to compare the efficacies of an amino acid jelly, Inner Power® (IP), and a liquid enteral product, Ensure Liquid® (EL), in terminally ill cancer patients. We randomly assigned patients to 3 arms: EL, IP, and EL+IP. The primary endpoint was drip infusion in vein (DIV)-free survival, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 14 publications
0
13
0
4
Order By: Relevance
“…However, no significant changes in anxiety or depression were observed. In our previous study, oral nutritional support with IP seemed to have a positive effect on QOL and survival in terminally ill cancer patients [38]. Cancer patients receiving chemotherapy experience physical exhaustion similar to terminally ill patients.…”
Section: Discussionmentioning
confidence: 97%
“…However, no significant changes in anxiety or depression were observed. In our previous study, oral nutritional support with IP seemed to have a positive effect on QOL and survival in terminally ill cancer patients [38]. Cancer patients receiving chemotherapy experience physical exhaustion similar to terminally ill patients.…”
Section: Discussionmentioning
confidence: 97%
“…Aspectos psicossociais da alimentação não são abordados em ferramentas de triagens e, portanto, questões como experiências sobre a ingestão de alimentos, bem como as barreiras enfrentadas ao alimentar-se, além do papel da família, dos cuidadores e dos alimentos para o paciente devem ser incluídas na rotina 16 , a fim de ampliar a visão quanto aos cuidados do paciente. Dessa forma, o apoio nutricional e orientações dietéticas relacionadas à quantidade, consistência e frequência de ingestão devem ser realizadas para o paciente e sua família, de modo que os auxiliem a lidar com questões que tangem à alimentação e seus obstáculos neste período 25 , visando manter ou recuperar o bem-estar do indivíduo 28 . Assim, o nutricionista é um dos profissionais responsáveis por oferecer recursos e esclarecimentos sobre o tratamento ao paciente e seus familiares 9 .…”
Section: Conteúdo Da Revisãounclassified
“…quanto ao volume, nutrientes e calorias conforme sobrevida e sintomatologia do doente 28 . Para determinar os objetivos e a efetividade da TN, é imprescindível considerar aspectos clínicos e psicológicos, funcionalidade, expectativa de vida, estado nutricional, aceitação e ingestão alimentar, além da integridade do trato gastrointestinal (TGI) 13 .…”
Section: Conteúdo Da Revisãounclassified
“…A small randomized controlled trial found that some patients could ingest nutritional supplements even in the final days of life. [40]Active measures may be undertaken to treat any potential nutritional impact symptoms and/or complications (Figure 1), providing that they are consistent with the patients’ goals of care. For example, pain control should be optimized and oral care should be provided regularly.…”
Section: Approach To Hydration and Nutrition In The Last Days Of Lifementioning
confidence: 99%
“…A small randomized controlled trial found that some patients could ingest nutritional supplements even in the final days of life. [40]…”
Section: Approach To Hydration and Nutrition In The Last Days Of Lifementioning
confidence: 99%